Aktivitas Antibakteri Ekstrak Daun Lintut (Hemigraphis sp) Terhadap Bakteri Eschericia coli, Staphylococcus aureus, Staphylococcus epidermidis, dan Salmonella typhi: Antibacterial Activities of Lintut Leaves (Hemigraphis sp) Extract Against Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, and Salmonella typhi Bacteria?s - Deva Ayudhia Septiani; Wisnu Cahyo Prabowo; Rolan Rusli (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Lintut plants are herbaceous plants that can grow in soft or watery soil. Research on leaf extracts against Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis and Salmonella typhi has never been done. This study aims to determine the antibacterial activity of leaf extract against Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis and Salmonella typhi. The research stages began with the manufacture of simplicia, the manufacture of ethanol extract of lintut leaves, the ethanol extract phytochemical screening test, and the antibacterial activity test using the well diffusion method. The study was conducted using 3 groups of concentrations of lintut leaf extract, namely 7%, 9% and 10% with ampicillin 0.1% as a positive control and aquadest as a negative control. The results of the phytochemical screening test showed that the leaf extract positively contained triterpenoids / steroids and tannins. Antibacterial activity using the well diffusion method showed that the extracts of lintut leaves with a concentration of 7%, 9% and 10% were not significantly different. The best concentration in inhibiting the growth of Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis and Salmonella typhi was at a concentration of 7%. The positive control used, namely ampicillin, produced a larger diameter of the inhibition zone compared to the diameter of the extract inhibition zone.